Oil and Protein Accumulation in Developing Seeds Is Influenced by the Expression of a Cytosolic Pyrophosphatase in Arabidopsis([C])([W])([OA]) - Meyer, Knut (American Society of Plant Biologists, 2012)
This study describes a dominant low-seed-oil mutant (lo15571) of Arabidopsis (Arabidopsis thaliana) generated by enhancer tagging. Compositional analysis of developing siliques and mature seeds indicated reduced conversion of photoassimilates to oil. Immunoblot analysis revealed increased levels of At1g01050 protein in developing siliques of lo15571. At1g01050 encodes a soluble, cytosolic pyrophosphatase and is one of five closely related genes that share predicted cytosolic localization and at least 70% amino acid sequence identity. Expression of At1g01050 using a seed-preferred promoter recreated most features of the lo15571 seed phenotype, including low seed oil content and increased levels of transient starch and soluble sugars in developing siliques. Seed-preferred RNA interference-mediated silencing of At1g01050 and At3g53620, a second cytosolic pyrophosphatase gene that shows expression during seed filling, led to a heritable oil increase of 1% to 4%, mostly at the expense of seed storage protein. These results are consistent with a scenario in which the rate of mobilization of sucrose, for precursor supply of seed storage lipid biosynthesis by cytosolic glycolysis, is strongly influenced by the expression of endogenous pyrophosphatase enzymes. This emphasizes the central role of pyrophosphate-dependent reactions supporting cytosolic glycolysis during seed maturation when ATP supply is low, presumably due to hypoxic conditions. This route is the major route providing precursors for seed oil biosynthesis. ATP-dependent reactions at the entry point of glycolysis in the cytosol or plastid cannot fully compensate for the loss of oil content observed in transgenic events with increased expression of cytosolic pyrophosphatase enzyme in the cytosol. These findings shed new light on the dynamic properties of cytosolic pyrophosphate pools in developing seed and their influence on carbon partitioning during seed filling. Finally, our work uniquely demonstrates that genes encoding cytosolic pyrophosphatase enzymes provide novel targets to improve seed composition for plant biotechnology applications.